2014
DOI: 10.1103/physrevb.90.140101
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electric-field-induced phase transition and piezoelectricity in lead zirconate titanate films

Abstract: We observed that electric field induces phase transition from tetragonal to rhombohedral in polycrystalline morphotropic lead zirconate titanate (PZT) films, as reported in 2011 for bulk PZT. Moreover, we evidenced that this field-induced phase transition is strongly correlated with PZT film piezoelectric properties, that is to say the larger the phase transition, the larger the longitudinal piezoelectric coefficient d 33,eff . Although d 33,eff is already comprised between as 150 to 170 pm/V, our observation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
2
26
1
Order By: Relevance
“…For example, a rhombohedral to orthorhombic ferroelectric‐ferroelectric phase transition occurring in (110) platelet of Pb(Mg 1/3 Nb 2/3 )O 3 crystal was induced by applying high electric field . Furthermore, a recent study demonstrated that the optimizing field‐induced phase transition in the morphotropic phase boundary (MPB) region was an effective approach to further improve the Pb(Zr, Ti)O 3 (PZT) film′s piezoelectric properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a rhombohedral to orthorhombic ferroelectric‐ferroelectric phase transition occurring in (110) platelet of Pb(Mg 1/3 Nb 2/3 )O 3 crystal was induced by applying high electric field . Furthermore, a recent study demonstrated that the optimizing field‐induced phase transition in the morphotropic phase boundary (MPB) region was an effective approach to further improve the Pb(Zr, Ti)O 3 (PZT) film′s piezoelectric properties …”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, a recent study demonstrated that the optimizing field-induced phase transition in the morphotropic phase boundary (MPB) region was an effective approach to further improve the Pb(Zr, Ti)O 3 (PZT) film 0 s piezoelectric properties. 11 However, lead-based ceramics have been confirmed to cause serious damage to the environment and human beings, thus it is urgent to explore nontoxic alternatives with superior electrical performances. With the development of leadfree piezoelectric materials in the past decades, K 0.5 Na 0.5 NbO 3 (KNN) is considered as one of the most promising candidates for replacing Pb-containing materials in future electronic devices since Saito et al amazingly discovered PZT-like properties associated with the MPB or polymorphic phase transition (PPT) near room temperature in (Li, Ta, Sb)-doped KNN textured ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…PbZr 0.2 Ti 0.8 O 3 (PZT) thin films (56 nm thick) were deposited on the Pt(100 nm)/TiO 2 (20 nm)/SiO 2 (500 nm)/Si substrate by the sol−gel method. 19 A Si wafer is chosen so that the process is as compatible as possible with the current semiconductor technology. The PbZr 0.2 Ti 0.8 O 3 stoichiometry was chosen to maximize the FE response of the material.…”
Section: Methodsmentioning
confidence: 99%
“…Field‐induced phase transitions have been reported to occur close to phase boundaries, which could induce an additional ferroelectric phase or change the phase fraction between the ferroelectric phases and lead to high piezoelectric properties in ferroelectric systems. In situ XRD measurements are often used to explore the field‐induced‐phase transition behavior in ferroelectrics . However, most in situ XRD studies are completed at, or near, room temperature due to limitations in the experimental setup.…”
Section: Introductionmentioning
confidence: 99%
“…In situ XRD measurements are often used to explore the field-induced-phase transition behavior in ferroelectrics. [18][19][20][21][22][23] However, most in situ XRD studies are completed at, or near, room temperature due to limitations in the experimental setup. Consequently, only limited selection of ferroelectric compositions can be used to study the field-induced-phase transition at room temperature since the phenomenon can only be observed close to phase boundaries.…”
Section: Introductionmentioning
confidence: 99%